Fast liquid chromatography method for separation of peptides using a sub‐2 μm ground silica monolith packed column. Issue 22 (26th September 2021) - Lu, Yao; Yan, Zhihong; Sun, Genlin
Abstract: A stationary phase based on sub‐2 μm ground silica monolith particles was fabricated by in situ polymerization and applied in micro‐column for separation of peptides. The sub‐2 μm silica particles were obtained from monolith using sol‐gel process followed by grinding and sedimentation to remove the fines. Initially, the silica monolith particles were pretreated with 3‐trimethoxysilyl propyl methacrylate to attach double‐bonded ligands onto the surface, then a network structure was formed onto the surface of the particle using styrene, N ‐isopropylacrylamide, and ethylene glycoldimethacrylate. The effect of the flow rate of the mobile phase on the separation performance was investigated. The stationary phase was characterized by field emission scanning electron microscopy, thermogravimetry, particle size distribution, and element analysis. The resultant phase was packed in glass‐lined stainless steel micro‐columns (2.1 mm × 50 mm) and evaluated for fast separation. An average number of theoretical plates as high as 9800 plates/column (5.10 μm plate height) was achieved for five synthetic peptides under the optimized flow rate of 0.15 mL/min. The repeatabilities of column‐to‐column, intraday, and interday through relative standard deviation were found better than 4%, exhibiting satisfactory repeatability of the developed micro‐column for fast separation of peptides.